2018
DOI: 10.3390/su11010108
|View full text |Cite
|
Sign up to set email alerts
|

A Tourist-Based Model of Authenticity of Heritage Sporting Events: The Case of Naadam

Abstract: As one of the important forms of intangible cultural heritage, heritage sporting events are becoming a potential catalyst of tourism. Commodification of heritage sporting events becomes popular for local authorities to boost economic development and express cultural authenticity, given that authenticity creates genuine performances and moving tourism experiences. However, commodification of heritage is a double-edged sword. It is a dilemma to commercialize a heritage sporting event while keeping its authentici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…Later, Bryce et al [41] expanded that model using the consumption of Japanese cultural heritage as a context, incorporating more preconceived notions and adding the concept of visitors' engagement to the relationship between authenticity and loyalty in their revised model. Zhang et al [14] proposed a tourist-based authenticity model for traditional sports events based on the categorization of "cold" and "hot" authenticities. In addition, scholars have found that feelings of dissonance and incongruity were generated in tourists when they came across inauthentic artifacts [21].…”
Section: Authenticitymentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Bryce et al [41] expanded that model using the consumption of Japanese cultural heritage as a context, incorporating more preconceived notions and adding the concept of visitors' engagement to the relationship between authenticity and loyalty in their revised model. Zhang et al [14] proposed a tourist-based authenticity model for traditional sports events based on the categorization of "cold" and "hot" authenticities. In addition, scholars have found that feelings of dissonance and incongruity were generated in tourists when they came across inauthentic artifacts [21].…”
Section: Authenticitymentioning
confidence: 99%
“…As heritage tourism is a form of travel with rich connotations, the issue of its authenticity has naturally attracted extensive attention from scholars who have undertaken academic research on TA. Using heritage sporting events (a form of intangible cultural heritage) as examples, Zhang et al [14] examined the relationship between authenticity, satisfaction, and loyalty. Jamal and Hill [15] pointed out that it was necessary to identify the tangible or intangible properties of objects, places, and spaces when comprehending the indicator framework for determining the authenticity of cultural heritage sites, while, at the same time, maintaining an awareness that these attributes are embedded in sociopolitical, interactive, and interconnected relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various types of ICH, traditional music, dance, and folklore are the most popular resources and have emerged as hotspots in ICH tourism research [7][8][9]. Related studies have addressed topics such as stakeholders, destinations, tourism products, heritage value, attractiveness, authenticity, tourist loyalty, and motivation [10][11][12][13].…”
Section: Current Status Of Ich Tourismmentioning
confidence: 99%
“…Due to the fuzziness of the concept itself, such significance has not been recognized in the implementation of the Convention. People tend to pay attention to the sustainability of only the heritage itself [48,49], ignoring the UN agenda of sustainable development. Most of the related studies are conducted as analyses of the relationship between ICH and some aspects of sustainable development in some cases.…”
Section: Intangible Cultural Heritage Tourism and Sustainabilitymentioning
confidence: 99%